Transcriptome analysis and identification of genes associated with leaf crude protein content in foxtail millet [Setaria italica (L.) P. Beauv.] - Cui, Yanjiao; Liu, Dan; Zhao, Zilong; Zhang, Jing; Li, Suying; Liu, Zhengli (Frontiers in Genetics, 2023)
Introduction: Spruce spider mite is a primary insect pest of Chinese chestnut in China and seriously influences its yield and quality. However, the current management against this mite is costly and poorly effective. In previous research, we bred several foxtail millet materials for interplanting with chestnut tree, and found that they had high levels of crude protein (CP) in leaves and attracted spruce spider mite to feed on the leaves, thereby reducing chestnut damage. Methods: In this study, four foxtail millet varieties with significant differences in leaf crude protein content were used for high-throughput sequencing and identification of genes associated with leaf crude protein content. Gene enrichment analyses were carried out to comprehend the functions of these genes and the biological processes in which they are involved. In addition, transcription factors (TFs) were evaluated. Results: 435 differentially expressed genes (DEGs) were identified, suggesting their potential role in crude protein accumulation. Some differentially expressed genes were found to be associated with nitrogen metabolism and ubiquitin-mediated proteolysis pathways. Moreover, we identified 40 TF genes categorized into 11 transcription factor families. Discussion: Our findings represent an important resource that clarifies the mechanisms of accumulation and control of leaf crude protein in foxtail millet, and provide an opportunity for suppression of spruce spider mite attack on Chinese chestnut by interplanting with foxtail millet varieties with high concentrations of leaf crude protein.